2017
DOI: 10.1016/j.landusepol.2017.01.051
|View full text |Cite
|
Sign up to set email alerts
|

Management of petroleum hydrocarbon contaminated sites in Nigeria: Current challenges and future direction

Abstract: Sites affected by petroleum hydrocarbons from oil exploitation activities have been identified as a major environmental and socioeconomic problem in the Niger Delta region of Nigeria. The current Nigerian regulatory instruments to manage these contaminated sites are fragmented and the roles and responsibilities of government agencies, such as the Department for Petroleum Resources (DPR), and the National Oil Spill Detection and Response Agency (NOSDRA), are not well defined. This lack of coordination has led t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 54 publications
0
42
0
3
Order By: Relevance
“…This study corroborates the findings in [ 21 ] that oil spill is a major impediment to agricultural activities in the Niger Delta region of the country. In addition, it provides an empirical impetus for the findings in [ 38 ] for the management of petroleum hydrocarbon contaminated sites in Nigeria. Nevertheless, several studies have shown that the pollution caused by oil spillage does not end with the mopping up of the spilled oil in the land area or water [ 39 ].…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…This study corroborates the findings in [ 21 ] that oil spill is a major impediment to agricultural activities in the Niger Delta region of the country. In addition, it provides an empirical impetus for the findings in [ 38 ] for the management of petroleum hydrocarbon contaminated sites in Nigeria. Nevertheless, several studies have shown that the pollution caused by oil spillage does not end with the mopping up of the spilled oil in the land area or water [ 39 ].…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Furthermore, the most fitting equation which depicts both the combine interactions and individual effects of the significant input variables (pH, moisture content, mass of substrate and turning rate) against the mesured response (TPH) is provided based on the coded variables and the actual factors which are shown in Eqs. 4and (5). Either of these two equations can be used in the estimation of the predicted TPH values which is shown in column 3 of Table 9.…”
Section: Input Parameters and Generated Equationmentioning
confidence: 99%
“…These activities have in one way or the other hampered the chain procedures of crude oil -drilling, refining, treatment, transportation and utilization which on the long run result in spillage, thus distorting several ecosystems and rendering most lands useless [3]. In Nigeria (especially the Niger Delta region comprising of nine states), there has been oil spills resulting in soil contamination due to poor operation and management practices [4,5]. It is reported that about 13 Mt of hydrocarbons are spilled which is caused largely by pipeline vandalism, destructive crude oil theft, operational spills and engineering failure (such as pipeline rupture), and uncivilized refining conditions [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…These activities have in one way or the other hampered the chain procedures of crude oil -drilling, re ning, treatment, transportation and utilization which on the long run results in spillage, thus distorting several ecosystems and rendering most lands useless [3]. In Nigeria (especially the Niger Delta region -comprising of nine states), there has been oil spills resulting in soil contamination due to poor operation and management practices [4,5]. It is reported that about 13 million tonnes of hydrocarbons are spilled which is caused largely by pipeline vandalism, destructive crude oil theft, operational spills and engineering failure (such as pipeline rupture), and uncivilized re ning conditions [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%